Respostas

2013-03-20T13:58:27-03:00

1º  3x+27=1-13

      3x=1-13-27

     3x=-39

      x=-39 

          3

      x= -13

2º 4x-28=2x+8

    4x-2x=8+28

     2x=36

       x=36

           2

      x=18

3º 3x+40=1x-12

    3x-1x=-12-40

    2x=-52

     x=-52

          2

      x= -26

4º 2x-18=1x+9

     2x-1x=9+18

      x=27

5º 2x+34=-3x-16

     2x+3x=-16-34

            5x=-50

             x=-50

                   5

             x= -10

6º 4x-24=3x+12

    4x-3x=12+24

          x=36

7º 5x+14=3x-6

    5x-3x=-6-14

          2x=-20

           x=-20

                 2

             x=-10

8º 2x-31=-1x+8

     2x+1x=8+31

            3x=39

              x=39

                   3

               x=13

9º 6x+15=-13+2x

    6x-2x=-13-15

         4x=-28

           x=-28

                 4

            x=-7

10º 5x-30=-15+2x 

       5x-2x=-15+30

            3x=15

              x=15

                    3

              x=5

1 5 1